Docetaxel enhances lysosomal function through TFEB activation - Zhang, Jianbin (Cell Death Dis, 2018)
Docetaxel is an effective and commonly used chemotherapeutic drug for cancer. Autophagy has been reported to be involved in the anticancer mechanism of docetaxel. However, the effect of docetaxel on lysosomal function remains elusive. In the present study, we first found that docetaxel treatment enhances autophagic flux in different cancer cells. Moreover, docetaxel treatment activates lysosomal function and promotes its fusion with autophagosome. Second, doctaxel treatment activates TFEB (transcription factor EB), a key nuclear transcription factor in control of lysosome biogenesis and function. We found that docetaxel promotes TFEB nuclear translocation and increases its transcriptional activity while knockdown of TFEB impairs lysosomal activation by docetaxel. Thirdly, TFEB activation by docetaxel is mediated by ROS (reactive oxygen species) generation and scavenging of ROS suppresses TFEB activity and lysosomal function in docetaxel-treated cells. Finally, inhibition of lysosomal function leads to increased docetaxel-induced cell death, suggesting that lysosomal activation protects against docetaxel-mediated apoptosis. Taken together, our results provide novel insights into the regulatory mechanisms of docetaxel on lysosomes, which could facilitate the development of novel potential cancer therapeutic agents via lysosomal inhibition.